ANALISIS STRUKTUR DAN NILAI MORAL DALAM CERITA RAKYAT ASAL USUL SENDANG SANI PATI - Nugroho, Femas Anggit Wahyu; Puspitasari, Riana Dewi; Putri, Nisa Wandiana; Muna, Salsabila Nailul; Kanzunnudin, Mohammad (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2023)
This study aims to analyze the structure and moral values in the folklore Origin of Sendang Sani. Structural analysis using the theory of Alan Dundes. Analysis of moral values uses the types of moral values in literary works according to Nurgiyantoro. The research method uses descriptive qualitative. Data collection was carried out through observation, interviews, documentation, recording, and transcription of the results of the interviews. The validity of the data is done by triangulation of sources, techniques, and time. Data analysis techniques use the Miles and Huberman models. The results of the study show that the story of the Origin of Sendang Sani has a structure of a combination of six motifs and is categorized as a folk tale with a very complex structure. As for the moral values contained, namely the value of the human relationship with himself includes (1) trying hard and (2) being honest, the value of human relations with the social and natural spheres includes (1) devotion and (2) friendship ties, the value of human relations with God includes ( 1) performing worship, (2) being patient, and (3) regretting and asking forgiveness for the sins that have been committed. Keywords:Folklore, Moral Values, Structural Analysis